Experiências de profissionais da saúde sobre identificação e manejo de risco ao psiquismo materno - Nogueira, Vanessa Trindade (2023)
Perinatality is a period that can be intensely experienced by women. Phase of great hormonal, physical and emotional changes caused by the pregnancy and care of a baby. The emotional condition of the pregnant/postpartum woman can influence the psychic constitution of the baby and the bond between the mother and the baby, so that paying attention to this moment in the woman's life is extremely relevant for the prevention of the health of the mother-baby duo. It is believed that one of the gateways to this work is primary care, through professionals who support women in prenatal care and child care. Based on this, a qualitative research was carried out with the objective of knowing the experiences of professionals who work in the line of maternal and child health care in primary care, focusing on the mental health of pregnant/postpartum women and their effects on the baby's psychic constitution. Professionals from a Family Health Strategy - ESF in Santa Maria, RS, were accessed through an interview with semi-structured questions. The analysis of the information took place from the content analysis following the precepts of Laurence Bardin (2016), with the construction of thematic categories. The research results will be presented in two articles. The first presents the perspective of health professionals on aspects of identification and management of psychic risk in perinatality. The second addresses the mental health of professionals and its impact on the care and management of pregnant and postpartum women. The research concluded that professionals are able to identify signs of psychic risk in the women assisted and demonstrate significant involvement with care, but seem to have difficulties in placing themselves in a position of emotional reserve. This difficulty seems to have an impact on the emotional health of professionals, overloading them and, consequently, harming the sharing of care with users and other members of the care network. It highlights the importance of a careful look for professionals who work in the identification and protection of pregnant and puerperal women who attend the primary care service, in order to strengthen the emotional support bases of professionals, thus contributing to the promotion of health in an expanded way, favoring the well-being and better management of both professionals in health spaces and service users.